Tasmania. ([Artarmon, N.S.W.] : Entertainment Publications)
Restaurant and activity guide that provides special discount and offers vouchers for many of the best restaurants, hotels and attractions. Entertainment Books are only available through fund-raising groups, organisations, and corporations as a member benefit or fund-raiser.
Title from cover.
Description based on: 2008/2009.
Keywords: Restaurants -- Tasmania -- Guidebooks; Hotels -- Tasmania -- Guidebooks; Entertainment events -- Tasmania -- Guidebooks; Retail trade -- Tasmania -- Guidebooks; Tasmania -- Description and travel -- Periodicals